Umbilical cord blood donation during caesarean section does not lead to increased maternal blood loss - Zaiss, Inka; Kehl, Sven; Petri, Elke; Helbig, Kathrin; Sütterlin, Marc; Siemer, Jörn (In vivo, 2010)
Background: Umbilical cord blood haematopoietic stem cell donation (UCBD) has increased in recent years. While performing UCBD during caesarean section, suturing the uterotomy is delayed for a few minutes. The aim of our study was to analyse if this causes an increase in maternal blood loss. Patients and Methods: In this retrospective study, we compared pre- and postpartal haemoglobin levels of 100 patients who delivered by caesarean, either with UCBD (study group) or without UCBD (control group). P-values ≤0.05 were regarded as significant. Results: The main clinical characteristics did not show any significant differences between the two groups. There was no significant difference of decrease in haemoglobin between the study group and the control group (p=0.747). Conclusion: UCBD during caesarean section does not lead to increased maternal blood loss. Objections to the safety of UCBD regarding increased maternal blood loss during caesarean section can be dispelled.
Gesehen am 08.05.2024
Kein DOI vorhanden